Temperature, thickness and discontinuity of permafrost - Kudryavtsev, V. A.; National Research Council Of Canada. Division Of Building Research (National Research Council of Canada, 1965)
This translation is the ninth arranged by the Permafrost Subcommittee of the Associate Committee on Soil and Snow Mechanics of the National Research Council of Canada, of Part I of the Russian permafrost publication, "Principles of Geocryology". This translation of Chapter VIII by V.A. Kudryavtsev describes the temperature regime at the ground surface and the seasonal freezing and thawing of the upper layer of the earth's crust. This is followed by a discussion of ground temperatures at the bottom of the layer with seasonal temperature variations. The influence of soil and rock type, bodies of water, and ground water on the thickness of permafrost are reviewed. The chapter concludes with an account of the influence of climatic and terrain features on the boundary conditions at the permfrost table and lower surface. : Ce document est la neuvième traduction consacrée à l'ouvrage russe intitulé Principes de géocryologie, qui est demandée par le Sous-comité du pergélisol du Comité associé de la mécanique des sols et de la neige du Conseil national de recherches du Canada. Cette traduction du chapitre VIII, écrit par V.A. Kydryavtsev, décrit le régime de températures à la surface du sol, ainsi que la congélation et le dégel saisonnier de la couche supérieure de la croûte terrestre. La suite comporte une discussion des températures relevées au fond de la couche en fonction des variations saisonnières de la température. L'auteur étudie également l'influence des types de sol et de roche, des masses d'eau et des eaux souterraines sur l'épaisseur du pergélisol. La fin du chapitre est consacrée à l'influence du climat et du relief sur les conditions limites observées au massif de pergélisol et sous la surface de ce dernier.